Assessment Policy and Impact on Practice : Sharpening the Policy Review in Australian Universities : Final Report. - Duck, Julie; Hamilton, Susan; Robb, Christina (Australian Learning and Teaching Council (ALTC), 2011)
Recent changes to institutional assessment policies have sought to align content, intended outcomes, pedagogies and assessment practices. This is the final report from a project that developed a set of practical guidelines for reviewing and analysing assessment policies in Australian universities. It focused on assessment policy review and analysis as a process, and a framework for review of learning and teaching policy was developed. The project sought to enhance university-level policy on assessment and inform the process of policy review. Using a case study at UQ, the project drew on archival data, analysis by stakeholders of narratives collected from students and staff about assessment experiences, analysis of environmental factors, identification of intended and unintended consequences of policy changes, engagement with staff across the university to assist with policy development and associated cultural change, and pilot studies of proposed changes. The project culminated in a national symposium which used the UQ experience as a basis for discussion of a way forward for the sector as a whole. The outcomes of the project were: a practical guide for universities seeking to review their assessment policy framework and a new draft assessment policy framework for UQ. Recommendations are included.